2011
DOI: 10.3109/13816810.2011.593606
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of Noonan syndrome

Abstract: The current study further supports the finding that ocular symptoms account for a large fraction of the clinical manifestations of NS. Additional characteristics are described here. The roles for the various mutations of PTPN11 in ocular development are yet to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Further investigations are required to explore the potential involvement of Shp2 mutations or associated polymorphisms in various retinal indices in both health and disease conditions. Indeed, many patients with Noonan Syndrome, of whom 50% typically harbor PTPN11 gene mutation (Tartaglia et al, 2002 ; Zenker et al, 2004 ), were identified with ocular abnormalities including fundal changes (Marin et al, 2012 ), optic disk excavation, enhanced cup to disk ratio and myopia, symptoms which are associated with higher risk of glaucoma and retinal degeneration (Whitmore, 1992 ; Marin et al, 2012 ; Lee and Sakhalkar, 2014 ). Applying genetic ablation of PTPN11 gene in animal studies resulted in extensive retinal degeneration, cell death and optic neuropathy during various developmental stages highlighting its regulatory function in retinal neuroprotection and progenitor retinal cell fate (Cai et al, 2011 ; Puri and Walker, 2013 ).…”
Section: Role Of Shp2 In Bdnf Mediated Survival Signalingmentioning
confidence: 99%
“…Further investigations are required to explore the potential involvement of Shp2 mutations or associated polymorphisms in various retinal indices in both health and disease conditions. Indeed, many patients with Noonan Syndrome, of whom 50% typically harbor PTPN11 gene mutation (Tartaglia et al, 2002 ; Zenker et al, 2004 ), were identified with ocular abnormalities including fundal changes (Marin et al, 2012 ), optic disk excavation, enhanced cup to disk ratio and myopia, symptoms which are associated with higher risk of glaucoma and retinal degeneration (Whitmore, 1992 ; Marin et al, 2012 ; Lee and Sakhalkar, 2014 ). Applying genetic ablation of PTPN11 gene in animal studies resulted in extensive retinal degeneration, cell death and optic neuropathy during various developmental stages highlighting its regulatory function in retinal neuroprotection and progenitor retinal cell fate (Cai et al, 2011 ; Puri and Walker, 2013 ).…”
Section: Role Of Shp2 In Bdnf Mediated Survival Signalingmentioning
confidence: 99%
“…NS is associated with a number of ocular anomalies. These include external features (e.g., ptosis, widely spaced eyes, downward-slanting palpebral fissures) as well as conditions like strabismus and nystagmus (Marin et al 2012). Refractory errors affect about 2/3 of individuals with NS (Lee et al 1992).…”
Section: Visual Processingmentioning
confidence: 99%
“…Anterior segment changes consisting of: Prominent corneal nerves, anterior stromal dystrophy, cataracts, and panuveitis. [ 17 18 ] Fundus changes including ONHD, optic disc hypoplasia, coloboma, and myelinated nerves. The diagnosis of Noonan syndrome is made purely on clinical grounds.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of Noonan syndrome was confirmed by the consultant pediatricians and clinical geneticists. [ 18 19 ]…”
Section: Discussionmentioning
confidence: 99%